Muscle forces and power are significantly reduced during walking in patients with peripheral artery disease. (April 2022) - Rahman, Hafizur; Anderson, Cody P.; Pipinos, Iraklis I.; Johanning, Jason M.; Casale, George P.; Dong, Jianghu; DeSpiegelaere, Holly; Hassan, Mahdi; Myers, Sara A.
Abstract: Patients with peripheral artery disease (PAD) have significantly reduced lower extremity muscle strength compared with healthy individuals as measured during isolated, single plane joint motion by isometric and isokinetic strength dynamometers. Alterations to the force contribution of muscles during walking caused by PAD are not well understood. Therefore, this study used simulations with PAD biomechanics data to understand lower extremity muscle functions in patients with PAD during walking and to compare that with healthy older individuals. A total of 12 patients with PAD and 10 age-matched healthy older controls walked across a 10-meter pathway with reflective markers on their lower limbs. Marker coordinates and ground reaction forces were recorded and exported to OpenSim software to perform gait simulations. Walking velocity, joint angles, muscle force, muscle power, and metabolic rate were calculated and compared between patients with PAD and healthy older controls. Our results suggest that patients with PAD walked slower with less hip extension during propulsion. Significant force and power reductions were observed in knee extensors during weight acceptance and in plantar flexors and hip flexors during propulsion in patients with PAD. The estimated metabolic rate of walking during stance was not different between patients with PAD and controls. This study is the first to analyze lower limb muscular responses during walking in patients with PAD using the OpenSim simulation software. The simulation results of this study identified important information about alterations to muscle force and power during walking in those with PAD.